Role of Women in Agriculture with Special Reference to WSHGs - Manoj Kumar Meher; Smaranika Pattnaik; Bimal Kumar Digal (Archives of Current Research International, 2025)
Women’s Self-Help Groups have significantly transformed the agricultural landscape and emerged as an influential platform for empowering women by providing them with financial independence, skill development, and improved access to agricultural inputs. Through collective action, women engaged in diverse activities, including sustainable farming, organic production, dairy farming, and agri-based entrepreneurship. The present study focuses on Sarlanji, a rural village in Lanjigarh Tehsil in the Kalahandi District of Odisha state using the data were collected by means of focused group discussions, and descriptive approaches were employed for interpretation. The results demonstrated a substantial transformation within the women’s community particularly in involvement in agricultural practices, increased in finance, education, capacity building, empowerment, and entrepreneurship, decision-making, and support males in income generation, reduced in distressed male migration and increased in child education. This underscores the central role of women in rural agricultural transformation and the achievement of five sustainable development goals: eradicating hunger, promoting gender equality and women’s empowerment, fostering inclusive and sustainable economic growth, and ensuring sustainable consumption and production.